Study Surface Roughness and Friction of Synovial Human Knee Joint with Using Mathematical Model - Abdullah, Enas Y; Edan, Naktal Moid; Kadhim, Athraa N (Al-Nahrain Journal of Science, 2018)
In this paper lubrication and friction of normal and diseased knee joint has been introduced. Various surface roughness of articular cartilage have been determined during the gait cycle (stance phase- swing phase) using squeeze film characteristics in knee joint, this paper aims to study the effects friction and roughness on stride length for male and female during daily activities. The mathematical model depends on the basis of the Stokes micro continuum theory, as well as we used lubricant (Newtonian - non Newtonian) in case of non-Newtonian (micro-macro) roughness effect has been studied and we compared effect film thickness of squeeze film lubrication in cycle time and roughness on pressure film, load carry capacity, in the elderly and young people for each sexes.